Construction and efficacy evaluation of novel swine leukocyte antigen (SLA) class I and class II allele-specific poly-T cell epitope vaccines against porcine reproductive and respiratory syndrome virus. (7th November 2020) - Tian, Debin; Subramaniam, Sakthivel; Heffron, C. Lynn; Mahsoub, Hassan M.; Sooryanarain, Harini; Wang, Bo; Cao, Qian M.; Hassebroek, Anna; LeRoith, Tanya; Foss, Dennis L.; Calvert, Jay G.; Meng, Xiang-Jin
Abstract : Porcine reproductive and respiratory syndrome virus (PRRSV) causes an economically important global swine disease. Here we report the development of subunit PRRSV-2 vaccines by expressing swine leucocyte antigen (SLA) class I and class II allele-specific epitope antigens in a robust adenovirus vector. SLA I-specific CD8 and SLA II-specific CD4 T cell epitopes of PRRSV-2 NADC20 were predicted in silico . Stable murine leukaemia cell lines (RMA-S), which are TAP-deficient and lacking endogenous class I epitope loading, were established to express different SLA I alleles. The binding stability of PRRSV T cell epitope peptides with SLA I alleles expressed on RMA-S cells was characterized. Two PRRSV poly-T cell epitope peptides were designed. NADC20-PP1 included 39 class I epitopes, consisting of 8 top-ranked epitopes specific to each of 5 SLA I alleles, and fused to 5 class II epitopes specific to SLA II alleles. NADC20-PP2, a subset of PP1, included two top-ranked class I epitopes specific to each of the five SLA I alleles. Two vaccine candidates, Ad-NADC20-PP1 and Ad-NADC20-PP2, were constructed by expressing the polytope peptides in a replication-incompetent human adenovirus 5 vector. A vaccination and challenge study in 30 piglets showed that animals vaccinated with the vaccines had numerically lower gross and histopathology lung lesions, and numerically lower PRRSV RNA loads in lung and serum after challenge compared to the controls, although there was no statistical significance. The results suggested that the Ad-NADC20-PP1 and Ad-NADC20-PP2 vaccines provided little or no protection, further highlighting the tremendous challenges faced in developing an effective subunit PRRSV-2 vaccine.